Identification of Screw Press Machine Malfunctions in PT. Ujong Neubok Dalam (UND) Using Failure Mode and Effect Analysis (FMEA) - Havid Maulana; T.M Aziz Pandria (LPPM Politeknik Aceh Selatan, 2023)
PT. Ujong Neubok Dalam (UND) is a company engaged in the business of plantation and processing of palm oil, the processing of palm oil into palm oil is carried out using a screw press. Screw press is a very important machine in processing palm oil into Crude Palm Oil (CPO), if the screw press has problems then the production process does not run smoothly. This study was conducted to identify damage and repairs to the working tools of the Screw Press machine. In the study using the Failure Mode Effect and Analysis (FMEA) method, which aims to identify risks in advance to take preventive measures. Based on the results of the study, there are 6 risks of failure in the Screw Press machine, with the component that has the highest result, namely the Screw of 108 and the component that has the smallest value, namely the Protection Hut, which is 12. From these results, it can be concluded that the Screw component is a priority or priority in making improvements.